Hidden threat of tortoise ticks: high prevalence of Crimean-Congo haemorrhagic fever virus in ticks Hyalomma aegyptium in the Middle East - Široký, Pavel; Bělohlávek, Tomáš; Papoušek, Ivo; Jandzik, David; Mikulíček, Peter; Kubelová, Michaela; Zdražilová-Dubská, Lenka (Parasites & vectors, 2014)
It is the first time that Crimean-Congo haemorrhagic fever virus (CCHFV), causing potentially lethal disease of humans, has been reported from the Middle East region and from the tortoise tick Hyalomma aegyptium from a tortoise host, whose epidemiological significance may have remained almost completely overlooked so far. We used RT-PCR to screen for 245 ticks collected from 38 Testudo graeca tortoise individuals. Results of our genetic screening provide unambiguous evidence of occurrence of CCHFV in this region and host, suggesting a potentially important role of H. aegyptium in CCHF epidemiology.
Keywords: Turtles; Sýrie; Ticks; Haplotypes; virus krymsko-konžské hemoragické horečky; haplotypy; Animals; Hemorrhagic Fever Virus, Crimean-Congo; Syria; Tick Infestations; Phylogeny; klíšťata; Turecko; zvířata; fylogeneze; želvy; infestace klíšťaty; Turkey